Stimulation of cell proliferation in the subventricular zone by synthetic murine pheromones - Koyama, Sachiko; Soini, Helena A.; Foley, John G.; Novotny, Milos V.; Lai, Cary (Frontiers in Behavioral Neuroscience, 2013)
Adult neurogenesis in female mice is known to be enhanced by exposure to soiled bedding from males, although the identity of the relevant chemosignals has remained unknown. Here we show that the previously recognized male murine pheromones, the farnesenes and 2-sec-butyl-4,5-dihydrothiazole (SBT), strongly increase cell proliferation in the subventricular zone (SVZ) of adult female mice, but not younger female mice. In addition, we found that a unique female murine pheromone, 2,5-dimethylpyrazine, facilitates similar changes in males. SBT stimulated cell proliferation in the SVZ of only adult females and not in young adult or pre- and post-puberty females. Our study suggests that pheromonal communication between males and females is enhancing reproductive success by controlling the estrous cycle and by promoting cell proliferation in a reciprocal manner.